Nicotine affects ethanol-conditioned taste, but not place, aversion in a simultaneous conditioning procedure - Loney, Gregory C. (2018)
The conditioned taste aversion (CTA) induced by ethanol is a key factor limiting ethanol intake. Nicotine, a drug co-consumed with ethanol, may decrease this aversion by modulating the unconditioned effects of ethanol or by disrupting the association between ethanol and its associated cues. This study analyzed ethanol-induced CTA and conditioned place aversion (CPA) in Long-Evans rats with subchronic exposure to nicotine. The rats were treated with nicotine (0.0 or 0.4 mg/kg) three times before conditioning (on lickometer training sessions 3, 4, and 5) and across conditioning days. During the conditioning the rats were given ethanol (1.3 g/kg) preceded and followed by presentation of a taste (NaCl) and tactile (rod or hole floors) conditioned stimulus (CS+), respectively. On CS− conditioning days, the rats were given vehicle and exposed to alternative stimuli. Three CTA and CPA testing sessions were then conducted. It was found that nicotine reduced ethanol-induced CTA and enhanced locomotor activity, but did not significantly modify the magnitude of ethanol-induced CPA. The effects of nicotine on CTA were observed during both conditioning and testing sessions, and were specific to the NaCl CS+, having no effect on reactivity to water. The dissociation between the effect of nicotine on ethanol-induced CTA and CPA suggests that nicotine does not alter ethanol's motivational properties by generally increasing its positive rewarding effects, nor does it blunt all aversive-like responses to this drug. Instead, nicotine may impede ethanol-induced CTA induced by ethanol by disrupting the neural underpinnings of this specific form of associative learning.